Comparison of the centering ability of the ProTaper Universal, ProFile and Twisted File Rotary Systems - Daniela de Andrade Mendes; Carlos Menezes Aguiar; Andréa Cruz Câmara (Universidade Estadual de Campinas, 2015)
Aim: To determine the centering ability of Twisted File™ rotary system compared with ProTaper Universal™ and ProFile™ rotary systems by evaluating pre- and postoperative cross-sectional images of the apical root canals third. Methods: Thirty mesiobuccal canals of human mandibular first molars were divided into three groups with 10 root canals each according to the instrument used: group 1, ProTaper Universal™ rotary system; group 2, ProFile™, and group 3, Twisted File™. Pre- and postoperative images of the apical thirds were viewed with a stereoscopic magnifier with ×10 magnification and were captured digitally for further analysis using the Image Tools Software. The results were analyzed statistically by the Kruskal-Wallis test and the MannWhitney test. A level of significance of 0.05 was adopted. Results: The means of the buccolingual measurement ranged from 0.79 to 1.5. The largest deviation was registered to instrument 25.06 in group 2. The means of the mesiodistal measurement ranged from 0.86 to 1.52, with the largest deviation being registered to instrument 25.04 in group 3; however, there were no statistically significant differences (p>0.05) among the three groups or among the instruments in the same group in terms of centering ability. Conclusions: None of the rotary systems evaluated in this study was totally effective in performing biomechanical preparation of the root canals.